Clinical Epidemiology and Risk Factors of Candida auris Bloodstream Infection in Trauma Patients. (October 2020) - Katoch, Omika; Bajpai, Vijeta; Khurana, Surbhi; Katyal, Sonal; Mathur, Purva
Abstract : Background: Candidiasis caused by Candida auris is one of the most serious hospital-acquired infection. Initially, Candida auris was reported to cause local infections; later, invasive candidasis was also reported in which the bloodstream, the central nervous system, kidneys, liver eyes, etc, are invaded. In this study, we evaluated the clinical epidemiology and risk factors in patients hospitalized to trauma center. Methods: This study was conducted at JPN Apex Trauma Centre of All India Institute of Medical Sciences, New Delhi, which is a 169-bed hospital. All patients who were identiﬁed to have candidemia due to C. auris over a period of 5 years from January 2012 to December 2016 were included. Blood samples were collected in BAC-T-Alert bottles (Bio Merieux, Durham, NC) and isolates were identiﬁed up to the species level by the VITEK 2 (version 8.01, BioMerieux). Conventional identiﬁcation was performed by observing color development on CHROMagar (Becton Dickinson, Franklin Lakes, NJ). The demographic and clinical data of patients were collected from the hospital information system. Results: Over a period of 5 years, 20 patients admitted to our trauma hospital developed candidemia due to Candida auris . Among them, men were predominant (95%), and the mean (SD) age of the patients was 33 (+15) years. Among these patients, 80% were in hospitalized and 20% were follow-up patients. The median of the total length of stay in the hospital was 34 days (range, 7–122). All of the patients were on mechanical ventilation; 65% patients were catheterized and 75% patients had central line placed. Head injury was the major cause of trauma followed by abdomen, chest, and spine. The overall mortality rate was 40%. Most of the patients (65%) who developed Candida auris infection were immunocompromised. The different comorbidities present were hypertension (35%), diabetes (15%), renal disease (10%), and hepatitis C (5%). Broad-spectrum antibiotics were given: amoxicillin-clavulanate was given to 65% of patients; cefoperazone sulbactam was given to 30% of patients; chloroamphenicol, amicillin-sulbactam, or clindamycin was given to 10% of patients. Antifungal agents like fluconazole or caspofungin were given to 5% of patients. Major surgeries like cranioplasty were performed in 58% of patients. Pancreatectomy, laparotomy, and endoscopic necrosectomy were performed in 42% of patients. Conclusions: Candida auris is one of the dreaded and most commonly spread hospital-acquired fungal infections, especially in immunocompromised patients. Broad-spectrum antibiotics use, major surgery, and invasive devices were the most common risk factors for acquiring Candida auris infection. Funding: None Disclosures: None